Motivations and Barriers Towards The Adoption of Click-And-Collect Service in Vietnam - Nguyen, Ngoc Nhu Quynh (2021)
The demand for a seamless and channel-agnostic shopping experience propels global merchants towards omni-channel retailing. Click-and-collect (C&C), a service that allows customers to place orders online and collect them at a physical pick-up point, is among the fulfilment option in an omni-channel environment. By investigating the market of Vietnam, this research discovers that the convenience to reach a pick-up station, service cost, perceived efforts paid and service compatibility are four factors with significant impacts on the intention to adopt C&C service of customers. Three factors with considerable influence on consumers usage frequency are convenience to access a pick-up location, service compatibility and perceived efforts. The second finding indicates that customers have different criteria for shopping methods in general and for C&C service in particular. While cost is the most essential element for Vietnamese people when selecting a shopping method, the convenience of accessing pick-up points has the greatest impact on C&C service uptake. By investigating the operational activities of two businesses providing C&C service in Vietnam, several insights can be gained. First, inconsistent implementation of C&C across industries has resulted in a slow rate of development and adoption. Second, the disparity in collection point network of some existing players obstructs service development. The findings are expected to be useful for setting up strategies to promote C&C service in Vietnamese market.